Study of Health Care Strategy During The Covid-19 Pandemic (Case Study at Puskesmas Purwodadi I Grobogan Regency) - Pratiwi Tedjo; Munawar Noor (CV. Ridwan Publisher, 2021)
The Physical Distancing and Work From Homr (WFH) policy is accountable to all areas including public services. The policy aims to trigger the eyes of the spread of this outbreak. Based on this, what was done in this study was a study on health care strategies during the Covid-19 pandemic in Purwodadi 1 Health Center, Grobogan regency. The purpose of the study was to find out what Health Care Strategy was developed by Purwodadi I health center during the Covid-19 pandemic. This assessment method is a descriptive method with a qualitative approach by using strength analysis, weaknesses, opportunity, thearth (SWOT). Data collection uses observations, in-depth interviews with established informants. The results of the study concluded that the health care strategy carried out by Puskesmas Purwodadi I has utilized the weaknesses that have been to capture better service opportunities as well as existing weaknesses facing challenges in health services during the Covid-19 Pandemic. The recommendation of the study results is cooperation between health centers, sub-districts, village heads, community leaders, to build public awareness is maintained. It needs to be developed by building collaboration between puskesmas (Government) with the Business World and Educational Institutions to develop open innovation in public services